Detailed analysis of in‐hospital costs for adult patients with type III intestinal failure: A single‐center study with global implications. Issue 3 (11th June 2021) - Siu, Adrian H. Y.; Carey, Sharon; Jones, Lynn; Morton, Rachael L.; Koh, Cherry E.
Abstract: Background: Home parenteral nutrition (HPN) is the recommended treatment for patients with type III intestinal failure (IF). However, owing to IF's rarity, the economic cost of managing these patients is not well understood. These patients often develop complications resulting in readmissions, which in turn contribute to ongoing costs. This study aims to document the costs of type III IF within the hospital, from initial admission, including readmissions, and to compare incurred costs with current government reimbursement. Methods: A retrospective study design reviewed costs and reimbursement for 25 consecutive patients commencing HPN at a quaternary hospital (October 2011 to September 2017). Hospital admissions were separated into the initial admission and readmission(s) period. Healthcare use and cost data were collected using electronic medical records. Hospital reimbursement costs were retrieved from Sydney Local Health District's Targeted Activity and Reporting Systems. Patient demographics were tabulated, and healthcare use and cost data were compared using Wilcoxon signed rank tests. Results: The median cost of the initial hospital admission was substantially higher than the median reimbursement (36, 675; interquartile range [IQR], 23, 196–67, 439 vs 19, 247; IQR, 7485–41, 090; P < .001). Similar results were observed in the readmissions period, with median incurred costs of 13, 898; (IQR, 11, 151–32, 130) vs reimbursement of 8469 (IQR, 5625–13, 078) ( P = .001). Conclusion: Results indicate that type III IF patients have high inpatient costs, which substantially outweigh current reimbursement. Improved funding models are needed to ensure hospitals that accept the management challenge of type III IF patients are not unduly penalized.